The association of metabolic syndrome with telomere length as a marker of cellular aging: a systematic review and meta-analysis - Ibraheem Shelash Al-Hawary, Sulieman; Ali Alzahrani, Abdullah; Ghaleb Maabreh, Hatem; Abed Jawad, Mohammed; Alsaadi, Salim B.; Kareem Jabber, Noura; Alawadi, Ahmed; Alsalamy, Ali; Alizadeh, Farideh (Frontiers in Genetics, 2024)
Background: It has been suggested that metabolic syndrome (MetS) accelerates the aging process, potentially contributing to the development of age-related complications. Available studies examining the relation of MetS to telomere length (TL), a putative biological marker of aging, have yielded inconclusive findings. This meta-analysis was performed to investigate the association between MetS and TL.Methods: A comprehensive systematic search was conducted in PubMed and Scopus databases to identify relevant literature published up to February 2024. Standard mean difference (SMD) and standardized beta coefficient (β) with their 95% confidence intervals (CI) were used as effect sizes to measure the associations using the random effects model.A total of 9 studies, comprising a total sample size of 8,606 participants, were eligible for the meta-analysis. No significant difference in mean TL was found between patients with and without MetS (SMD= -0.03, 95%CI= -0.17 to 0.10), with a significant heterogeneity across the studies (I 2 = 89.7.0%, P ≤ 0.001). In contrast, it was revealed that MetS is negatively related to TL (β= -0.08, 95%CI= -0.15 to -0.004). In the subgroup analysis, this finding was supported by the International Diabetes Federation (IDF) definition of MetS.This meta-analysis highlighted that MetS may be linked to a shorter TL.Additional studies are required to confirm this finding.